IMPLEMENTASI DANA ZISWAF DALAM PENDIDIKAN ISLAM - Dewi, Irawati; Bukhori, Iqbal; Sopwandin, Iwan; Hidayat, Ara (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2020)
This study aims to explain the practice of using waqaf funds as a source of funding in Islamic education. The research method used is descriptive analysis through literature study data collection techniques. The results of this study revealed (1) Waqaf became one of the sources of educational funding in the golden age of Islam in the classical era (2) The basic potential of waqaf in Indonesia was highly qualified as one of the sources of educational funding, namely Rp. 3 trillion per year (3) There are positive contributions from the allocation of waqaf funds in the practice of financing Islamic education in Indonesia, one of the actualisations is the establishment of the Smart Exelensia School, the Islamic School of Islam, the pen circle reading house, and Darusalam Scholarship.